Generalized preparation of Au NP @ Ni(OH)2 yolk-shell NPs and their enhanced catalytic activity. (May 2020) - Cai, Ren; Jin, Haiyan; Yang, Dan; Lin, Keng-Te; Chan, Kitying; Sun, Jianke; Chen, Zhuo; Zhang, Xiaobing; Tan, Weihong
Abstract: Yolk-shell nanostructures have attracted considerable attention because of their unique properties and promising applications. Yet, synthesis of well-defined yolk-shell structures with controllable composition remains a major challenge. Here, we report a general method to fabricate Au NP @ Ni(OH)2 yolk-shell NPs. Au cores with various diameters and shapes can be successfully encapsulated into the Ni(OH)2 shells by a similar approach. When the diameter of the core Au NPs changed from 15 to 90 nm, the size of the yolk-shell NPs accordingly grew from 110 to 380 nm, however, the shell thickness of the final yolk-shell NPs is in the narrow range of 18–20 nm. The synergistic contribution from both Au and Ni(OH)2 has endowed the yolk-shell heterostructure with enhanced catalytic activity. As shown in the oxygen-evolution reactions (OER) tests, the OER activity of Au NP @ Ni(OH)2 yolk-shell NPs is 8.7 and 86-fold higher than that of hollow Ni(OH)2 NPs alone and Au NP @C (5%) (Au NPs (5%) mixed with Carbon Black), respectively. In general, our method provides a simple and novel strategy towards the fabrication of yolk-shell structures with superior catalytic activity for OER. Graphical abstract: Au NP @ Ni(OH) 2 yolk-shell NPs : were synthesized by simultaneous etching of Cu2 O NPs and formation of Ni(OH)2 shells. The diameters of these yolk-shell NPs is 380 nm, and the thickness of the shells is 20 nm. The yolk-shell NPs possess superior catalytic activity for OER. Image 1 Highlights: The most important point in this work is the controllable preparation of Au NP @ Ni(OH)2 yolk-shell NPs through based on simultaneous etching of Cu2 O NPs and formation of Ni(OH)2 shells. As-developed fabrication route of yolk-shell NPs is a general approach. The Au NP @ Ni(OH)2 yolk-shell NPs demonstrate enhanced performance for oxygen-evolution reactions (OER) activity.